Puget Sound Navigation Company passenger steamer UTOPIA and O.S.K. freight steamer SEATTLE MARU at dock in Seattle, probably 1909 (1909)
PH Coll 794.116 The wooden steamer UTOPIA was built in Seattle in 1893 for G.W. McGregor to replace the J.R. MCDONALD on the Seattle-Vancouver freight run. The UTOPIA registered 423 tons and was 124 feet long. On August 20, 1896 she was involved in a single-fatality collision with the steamer FLYER, although neither vessel was damaged beyond repair. Starting in 1898 the Seattle Steamship Co. operated the UTOPIA on a twice-monthly Puget Sound-Skagway-Dyea service carrying 24 first-class and 54 steerage passengers. By 1902 the vessel was in operation with the La Conner Trading & Transportation Co., which merged with the Puget Sound Navigation Co. in 1903. On October 14, 1908, the vessel caught fire enroute from Bellingham to Seattle, but the vessel was successfully beached. There were no injuries and the vessel was repaired. The UTOPIA was chartered by Harold Lloyd for the filming of the 1925 picture Winds of Chance. In 1926 she was sold and scrapped. (Source: Newell, Gordon, ed. "The H.W. McCurdy Marine History of the Pacific Northwest." Seattle: The Superior Company, 1966.) The freight steamer SEATTLE MARU was operated by Japan's Osaka Shosen Kaisha on Pacific Northwest-Japan routes. (Source: Newell, Gordon, ed. "The H.W. McCurdy Marine History of the Pacific Northwest." Seattle: The Superior Company, 1966.) To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number